1998
DOI: 10.1021/ma971491j
|View full text |Cite
|
Sign up to set email alerts
|

Semicrystalline Polymers via Ring-Opening Polymerization:  Preparation and Polymerization of Alkylene Phthalate Cyclic Oligomers

Abstract: Preparation of cyclic oligomeric alkylene phthalates via pseudo-high dilution condensation of alkylene diols with iso- and terephthaloyl chlorides and conversion to high molecular weight polyesters via ring-opening polymerization is described. Sterically unhindered amines such as quinuclidine or 1,4-diazabicyclo[2.2.2]octane (DABCO) catalyze the condensation significantly faster than other tertiary amines and are useful for carrying out this conversion in high yield, in the first direct reaction of diol and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
156
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(180 citation statements)
references
References 24 publications
13
156
0
4
Order By: Relevance
“…This distribution of cycle sizes was in all cases close to that reported by Brunelle et al [7] for a cyclic fraction prepared by reaction of terephthaloyl chloride with hexamethylene glycol in solution at high dilution conditions. Such fraction consisted of species ranging from the dimer to the heptamer with percentage contents decreasing with the increase of cycle size.…”
Section: Synthesis and Characterization Of C(ht) 2-5 By Cyclo-depolymsupporting
confidence: 89%
See 4 more Smart Citations
“…This distribution of cycle sizes was in all cases close to that reported by Brunelle et al [7] for a cyclic fraction prepared by reaction of terephthaloyl chloride with hexamethylene glycol in solution at high dilution conditions. Such fraction consisted of species ranging from the dimer to the heptamer with percentage contents decreasing with the increase of cycle size.…”
Section: Synthesis and Characterization Of C(ht) 2-5 By Cyclo-depolymsupporting
confidence: 89%
“…found that each hexamethylene terephthalate cyclic oligomer of M mass was accompanied by a minor amount of the M+100 compound, which was identified by NMR as the corresponding oligomer with one hexamethylene glycol unit replaced by one di(hexamethylene glycol) unit. As it can be expected, these di(hexamethylene glycol) containing oligomers were not reported to be present in the cyclic fractions produced by chemical synthesis from diadic chlorides and diols due to milder conditions used for the synthesis [7].…”
Section: Synthesis and Characterization Of C(ht) 2-5 By Cyclo-depolymmentioning
confidence: 83%
See 3 more Smart Citations